2021
DOI: 10.1111/acer.14756
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life is dynamic in alcoholic hepatitis and responds to improvement in liver disease and reduced alcohol consumption

Abstract: Background The impact of alcoholic hepatitis (AH) on health‐related quality of life (HRQOL) remains inadequately described. We aimed to characterize HRQOL in AH and heavy drinkers (HD), and its associations with clinical variables and outcomes. Methods This is a post hoc analysis of participants in the Translational Research and Evolving Alcoholic Hepatitis Treatment 001 study (NCT02172898). HRQOL was measured using Short Form Health Survey (SF‐36). Mean SF‐36 scores were compared in AH and HD with two‐sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…105 Independent of the severity of the clinical disease this improvement was also correlated with a decrease in mortality. 105 Partnership with patients is as vital as multidisciplinary care in AUD therapy and thus continued research into interventions that impact factors important to the patient, such as quality of life and reduction of healthcare stigma, will need to be an ongoing focus.…”
Section: Tre Atment For Audmentioning
confidence: 93%
See 2 more Smart Citations
“…105 Independent of the severity of the clinical disease this improvement was also correlated with a decrease in mortality. 105 Partnership with patients is as vital as multidisciplinary care in AUD therapy and thus continued research into interventions that impact factors important to the patient, such as quality of life and reduction of healthcare stigma, will need to be an ongoing focus.…”
Section: Tre Atment For Audmentioning
confidence: 93%
“…As with most chronic liver disease, patients with ALD report a lower quality of life than those without chronic liver disease. A recent study analysing the quality of life metrics longitudinally showed that patients with ALD tended to have lower mental quality of life metrics than those with other chronic liver disease and that this improved over time with the achievement of abstinence 105 . Independent of the severity of the clinical disease this improvement was also correlated with a decrease in mortality 105 .…”
Section: Treatment For Audmentioning
confidence: 99%
See 1 more Smart Citation